ЭТНОПСИХОЛОГИЧЕСКИЕ ОСОБЕННОСТИ КОММУНИКАТИВНЫХ КАЧЕСТВ ЛИЧНОСТИ УЧАЩИХСЯ НАЧАЛЬНЫХ КЛАССОВ - Клычева, З.П. (SCIENCE and SOCIETY, 2024)
This article presents the results of analyzes of research using R. Cattell’s method on the communicative qualities of personality in students from grades 1 to 4 with karakalpak and russian languages of instruction.